Recent developments in quantitative models of sovereign default - Nikolai Stähler (Deutsche Bundesbank, 2011)
The current crisis and discussions, in the euro area in particular, show that sovereign debt crises/defaults are no longer restricted to developing economies. After crises in many Latin American countries, the literature on quantitative dynamic macro-models of sovereign default has been advancing. Current debate should take notice of the findings from this literature - an extensive overview of which has been provided in this paper. This paper also discusses the difficulties involved in, but also possibilities of, integrating this type of model in standard business cycle models (RBC and DSGE models). This is likely to be particularly helpful when using models to analyse upcoming issues in the euro area, such as a suitable (sovereign) insolvency law or the assumption of joint liability.
Keywords: F34; F41; E21; E32; G10; 330; Sovereign Debt; Default Risk; Endogenous Borrowing Constraints; Small Open Economy; Staatsbankrott; Öffentliche Schulden; Verschuldungsrestriktion; Wirtschaftsmodell; Real Business Cycle; Dynamisches Gleichgewicht; Kleines-offenes-Land; Theorie